Ecology in the Qur’an: Principles of Sustainability and Nature Conservation in Pikukuh Baduy - Hamdie, Muhamad Zaky; Al Ayubi, Sholahuddin (Jurnal Keilmuan dan Keislaman, 2025)
This study explores the ecological principles of the Qur’an, focusing on sustainability and nature conservation as a moral and spiritual framework for addressing contemporary environmental challenges. As climate change, biodiversity loss, and ecological degradation intensify globally, the integration of religious perspectives into environmental ethics becomes increasingly significant. The primary aim of this research is to examine Qur’anic teachings on how humans should interact with the environment and manage natural resources responsibly. Using a qualitative thematic analysis, the study identifies and interprets relevant verses that emphasize humanity’s role as khalifah (stewards) on earth, the prohibition of excess and waste, and the importance of maintaining ecological balance. The findings indicate that the Qur’an provides a comprehensive ethical foundation for sustainability, highlighting values such as justice, prudence, accountability, and compassion. These principles are not only spiritually meaningful but also practically relevant in shaping sustainable behaviors, policies, and community initiatives. Furthermore, the incorporation of indigenous wisdom, such as the Pikukuh Karuhun of the Baduy community, illustrates how Qur’anic ecological ethics can be harmonized with local traditions to promote holistic environmental stewardship. Overall, this research demonstrates that Qur’anic teachings extend beyond spiritual guidance to offer practical solutions for environmental preservation. By integrating spiritual values with sustainability practices, individuals and communities can enhance ecological awareness, foster collective responsibility, and contribute to the creation of a more just, balanced, and sustainable world for present and future generations.